AN ANALYSIS OF TRAUMA OF THE MAIN CHARACTER IN ROOM MOVIE - Arif Hidayat; Ines Indarujati (Ennichi, 2020)
The objectives of this study is to know information about trauma, especially some types of trauma shown, some symptoms of trauma in ‘Room’ movie. This study uses descriptive method with qualitative as its approach. The data of this study are the dialogues and scenes of Room movie by Lenny Abrahamson. Using the theory of Briere and Scott (2016) as the measurement, the result of the study shows that there are two types of trauma found i.e. stranger physical assault and torture.On the other hand, by having the theory given by Jaffe, Segal and Dumke (2016) in analyzing the symptoms, it is found that the symptoms of trauma are physical, emotional and cognitive. Meanwhile, the treatment to main character’s trauma are medication and family intervention.